Changing trends of obesity and lipid profiles among Bangkok school children after comprehensive management of the bright and healthy Thai kid project - Chutima Sirikulchayanonta; Vorachai Sirikulchayanonta; Kanjana Suriyaprom; Rachanee Namjuntra (BMC, 2022)
Abstract Background Cardiovascular diseases are the world's leading cause of death. Children in Thailand are currently facing obesity, hyperlipidemia, and high atherogenic indices. This study aimed to assess the success of the Bright and Healthy Thai Kid project in reducing obesity and high lipid profiles among Bangkok school children. Methods A community-based, intervention (participatory action) with pre-post comparison of anthropometric and lipid profile data was conducted in five randomly selected Bangkok primary schools. The participatory action involved teachers, students, and parents. Data collection on anthropometric measurements, dietary intake, physical activity, and fasting blood samples of three generations of students was carried out during July-August (midterm months in Thailand) in the years 2004, 2017, and 2019. SPSS for Windows, version 16 was used for data analysis. Results Comparing the data from 2004, 2017, and 2019, obesity rates of 19.3 in 2004 gradually declined to 16.9 and 15.6 in 2017 and 2019 (P <  0.001). High serum total cholesterol, triglyceride, LDL-C, and atherogenic indices decreased significantly (p <  0.001). Conclusions We believe that the great time and effort expended for a campaign to reduce rates of obesity and hyperlipidemia in school children does work to prevent future cardiovascular diseases. Long-term investment in national programs is required to achieve whole societal involvement in improving knowledge and skills related to health, nutrition, and healthy food choices.